Optimization and validation of multiresidual extraction methods for pharmaceuticals in Soil, Lettuce, and Earthworms - Mravcová, Ludmila; Amrichová, Anna; Navrkalová, Jitka; Hamplová, Marie; Sedlář, Marian; Gargošová, Helena Zlámalová; Fučík, Jan (Environmental science and pollution research international, 2024)
The presence of human and veterinary pharmaceuticals (PhACs) in the environment poses potential risks. To comprehensively assess these risks, robust multiresidual analytical methods are essential for determining a broad spectrum of PhAC classes in various environmental compartments (soil, plants, and soil organisms). This study optimized extraction methods for analyzing over 40 PhACs from various matrices, including soil, lettuce, and earthworms. A four-step ultrasonic extraction method with varying extraction conditions and subsequent solid phase extraction was developed for soil samples. QuEChERS methods were optimized for extracting PhACs from lettuce and earthworm samples, addressing a literature gap in these less-studied matrices. The quantification of PhACs in soil, lettuce, and earthworm extracts was performed using a single LC-MS/MS method. Following thorough method validation, earthworms and lettuce were exposed to a mixture of 27 pharmaceuticals in a soil environment. The method validation results demonstrated the robustness of these methods for a broad spectrum of PhACs. Specifically, 29 out of 42 PhACs were extracted with an average efficiency > 50% and RSD < 30% from the soil; 40 out of 42 PhACs exhibited average efficiency > 50% and %RSD < 30% from the earthworms, while 39 out of 42 PhACs showed average efficiency > 50% and RSD < 30% from the lettuce. Exposure experiments confirmed the viability of these methods for quantifying a diverse range of PhACs in different environmental compartments. This study presents three thoroughly validated methods for determining more than 40 PhACs in diverse matrices, enabling a comprehensive assessment of PhAC dissemination in the environment.
Keywords: Oligochaeta; Chromatography, Liquid; Pharmaceutical Preparations; Liquid chromatography; salát (hlávkový); tandemová hmotnostní spektrometrie; Lactuca; látky znečišťující půdu; Solid-phase extraction; QuEChERS; chromatografie kapalinová; Soil; Soil Pollutants; léčivé přípravky; extrakce na pevné fázi; Animals; zvířata; Pharmaceutical pollution; Mass spectrometry; Tandem Mass Spectrometry; půda; Solid Phase Extraction; Multiresidual analytical methods